PROTOCOLS FOR DENTAL EMERGENCIES DURING A PANDEMIC: Akhmedov Ilkhom Ibrokhimovich, Ruzieva Gulchekhra Atoevna, Tursunova ShahzodaSharof kizi - Doctoral student of Bukhara State Medical Institute, Akhmedov Ilkhom Ibrokhimovich; Senior teacher of the Afshona Public Health Technical College named after Abu Ali Ibn Sina, Ruzieva Gulchekhra Atoevna; Afshona Public Health Technical College named after Abu Ali Ibn Sina is the head of the department, Tursunova ShahzodaSharof kizi (Лучшие интеллектуальные исследования, 2024)
Given the challenges posed by the pandemic, dental clinics are restricted to providing care only in emergency situations. This limitation may be distressing for patients experiencing acute pain if their condition does not qualify as an emergency. It is essential to study the practices of international colleagues to define dental emergencies and determine how to administer treatment under pandemic conditions. Guidelines from WHO, the Ministry of Health, the American Dental Association, and the Royal College of Dental Surgeons of Ontario for emergency admissions during the pandemic are used as references.